Relevance of the idea of family homesteads in the context of social and economic development of the country - Chaikouskaya, Rehina U. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article presents the results of sociological study on the topic of family homesteads in Belarus, which was conducted online in May 2021. The relationship between successful implementation of the idea of family homesteads and successful implementation of indicators for the main program of social and economic development of the country and the number of other state programs of the Republic of Belarus is shown.